Health Monitoring System for Diabetic Patients (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Diabetes is one of the main universal health problems. consistent with the World health organization report, around 346 million people worldwide are affected by DM. DM may be a metabolic disease where the inappropriate controlling of blood sugar levels causes the danger of many diseases like attack, renal disorder, and kidney failure. In DM, the body doesn’t properly use the insulin hormone secreted by the pancreas gland. There are numerous computerized methods for the diagnosis of DM but the most drawback of those methods is that the patient has got to undergo several medical tests to give the input values to the computerized recognizing system which proves to be high cost and time taking process. With the rapid advancement within the field of AI, there are numerous techniques and algorithms during AI mostly used for the prediction and identification of various diseases. These algorithms in AI convince to be cost-effective and time saving for diabetic patients and doctors. In the proposed model we are recognizing diabetes using K Nearest neighbor algorithm which is most dominant model of Artificial Intelligence.